From Soldiers to Students: The Tests of General Educational Development (GED) as Diplomatic Measurement. Issue 4 (13th October 2017) - Hutt, Ethan L.; Stevens, Mitchell L.
Abstract : The GI Bill's college-attendance provisions posed an evaluation problem. How would returning veterans, most of whom were without high school diplomas, be judged fit for college? Drawing from a variety of primary source material from the years surrounding the close of World War II, we show how leaders in government, the military, and academia cooperated to produce a measure of college fitness that would deem virtually all veterans fit for college entry. We use this historical moment to develop a novel theoretical insight. Measurement is diplomatic when it facilitates transactions across institutional distinctions while recognizing and honoring those distinctions. This insight has broad utility for students of American political development.